Drug addiction & the rehabilitation process - Samarakoon, M.; Wasantha, H.P.C.; Wijewardhana, B.V.N.; Senarathna, P (My University, 2018)
The impact of drug addiction is large and it has its consequences for families, health, education, crime and employment in any society. Unlike in any other issue at hand, drug misuse is penetrated into society from macro to micro level creating lots of social, psychological, economical and health hazards for the public. Individuals of long term drug addiction have to go through serious health hazards risking even their lives. On the other hand, the families of these individuals are experiencing serious psychological, social and economic hardships due to the addiction of their loved one. In this perspective, this study observes the nature of drug addiction and the rehabilitation process of the drug rehabilitation in Sri Lanka. The research problem of the study was to examine whether why drug adductors relapsing in the rehabilitation process. The study was based on both primary and secondary data. The primary data has been collected from two rehabilitation centers that conducted by government entity in Sri Lanka. Collection of data was an integral part of the study and consequently, numerous sources of data were used such as structured questionnaires, observations, interviews and informal discussions. Data interpretation was done using both qualitative and quantitative measures. It was observed that as a whole, the rehabilitation process is effective and the program has adopted the most mandatory features characterized in a successful in-house rehabilitation program. Though, Infrastructural facilities should be uplifted for both rehabilitees and the rehabilitation staff. Further facilities and trained counselors should be provided to address mental health issues of rehabilitees.
A psycho-social study of drug offenders in Sri Lanka
Keywords: addiction, drugs, process, psycho-social study, rehabilitation